Efficacy and safety of antithrombotic regimens after coronary intervention in patients on oral anticoagulation: Traditional and Bayesian meta-analysis of clinical trials. (15th February 2016) - Liu, Jian; Fan, Meida; Zhao, Jingjing; Zhao, Bingcheng; Zhang, Chongyu; Liu, Chen; Dong, Yugang
Abstract: Objective: To perform a systematic review and meta-analysis to assess the efficacy and safety of diverse antithrombotic regimens in patients on long-term anticoagulation after percutaneous coronary intervention (PCI). Methods: After searching electronic database (up to 27 June 2015), we included trials comparing dual antiplatelet therapy (aspirin plus clopidogrel), oral anticoagulant (OAC) plus clopidogrel, OAC plus aspirin, or triple therapy (OAC with clopidogrel and aspirin). Efficacy outcomes were major adverse cardiovascular event (MACE), ischemic stroke, myocardial infarction (MI), and all-cause mortality; safety outcomes included major bleeding and any bleeding. We conducted both traditional and Bayesian network meta-analysis, computing pooled odds ratio (OR) with 95% confidence intervals (CI) to compare diverse antithrombotic therapies simultaneously. Results: Eighteen trials were included in the quantitative analysis. OAC plus clopidogrel and triple therapy were associated with a lower risk of MACE, ischemic stroke, MI and all-cause mortality compared with dual antiplatelet or OAC plus aspirin regimens. OAC plus clopidogrel was ranked the most efficacious option without an increase in bleeding episodes. However, triple therapy improved the efficacy outcomes at the expense of increasing hemorrhage. For the initial short-term outcomes, OAC plus clopidogrel inconclusively reduced the risk of MACE and had a significantly lower risk of any bleeding. Conclusions: OAC plus clopidogrel may be the optimal antithrombotic therapy in patients on oral anticoagulation undergoing PCI, which has equal or better efficacy outcomes without increasing the rates of bleeding episodes. Moreover, we found initial triple therapy to be unnecessary as it increased the risk of bleeding.